Catalytic Synthesis and Antifungal Activity of New Polychlorinated Natural Terpenes - Hana Ighachane; Brahim Boualy; Mustapha Ait Ali; My. H. Sedra; Larbi El Firdoussi; Hassan Bihi Lazrek (Advances in Materials Science and Engineering)
Various unsaturated natural terpenes were selectively converted to the corresponding polychlorinated products in good yields using iron acetylacetonate in combination with nucleophilic cocatalyst. The synthesized compounds were evaluated for their in vitro antifungal activity. The antifungal bioassays showed that 2c and 2d possessed significant antifungal activity against Fusarium oxysporum f. sp. albedinis (Foa), Fusarium oxysporum f. sp. canariensis (Foc), and Verticillium dahliae (Vd).